Management of Postpartum Hemorrhage, Risk Factors, Urological Implications, and Maternal Outcomes: A Clinical Evidence-Based Study - Zahra Elbukhari Mohammed Ahmed Ali, Uzma Noreen, Awais Ayub, Ibtisam Nawaz Minhas, Munawar Afzal, Humaira Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postpartum hemorrhage (PPH) is a significant contributor to maternal morbidity and mortality, specifically in low-resource settings like Pakistan. The advent of obstetric care has not removed the challenges of inadequate emergency response and insufficient blood transfusion. The risk factors, management strategies, urological complications, and maternal outcomes associated with PPH are evaluated in this study in a tertiary care setting. Objectives: The study aimed to analyse prevalence of PPH risk factors, effectiveness of medical and surgical management, associated urological complications, and maternal outcomes in Pakistani women. Methods: This retrospective study was conducted in tertiary care hospitals in Pakistan from August 2021 to August 2022, including a total of 100 postpartum hemorrhage (PPH) cases. Data on maternal demographics, risk factors, management approaches, and outcomes were analyzed using descriptive statistics in SPSS version 25.0. A p-value of <0.05 was considered statistically significant. Results: The most common cause of PPH was uterine atony (45%), then placental abnormalities (15%), hypertensive disorders (12%), and previous cesarean delivery (32%). The most commonly used were oxytocin (92%) and misoprostol (70%), and 60% of cases required blood transfusions. In severe cases, surgical interventions, such as uterine tamponade (18%) and hysterectomy (6%) were employed. Acute kidney injury (10%) was the most frequent urological complication, but 25% of cases had complications involving the urological system. Eighty percent of maternal outcomes recovered, 12 percent required extended hospitalization, 6 percent were admitted to the ICU, and 2 percent died. Conclusion: In Pakistan, PPH is still a major obstetric challenge. Maternal morbidity and mortality can be reduced by strengthening emergency obstetric care, improving blood transfusion availability, and standardizing PPH management protocol. Keywords: Postpartum hemorrhage, uterine atony, cesarean section, hypertensive disorders, placental abnormalities, blood transfusion, urological complications, maternal mortality, obstetric emergency, Pakistan.